Weaving A New Paradigm: Transforming Islamic Education Under The Aegis Of The Independent Curriculum - Sarwoedi; Syamsir; Fakhruddin; Lukman Asha; Jumira Warlizasusi (Jurnal Manajemen Pendidikan Islam Darussalam, 2025)
This study analyzes and identifies forms of innovation in the learning process of Islamic education within the Merdeka Curriculum framework. Innovation in the implementation of the Merdeka Curriculum is a response to the challenges of the relevance of Islamic education in the digital era. This study uses a qualitative approach with library research, focused on analyzing relevant literature regarding learning innovations in Islamic education based on the Merdeka Curriculum. Data collection techniques were conducted through document studies of scientific papers published in the last five years. The results of the study indicate that innovations in the learning process of Islamic education, such as differentiated learning, Project-Based Learning, and the integration of digital technology, contribute to increased student engagement, understanding of Islamic values, and strengthening teacher capacity. However, challenges were also identified in the form of limited infrastructure and cultural resistance among educators. This study recommends strengthening teacher training and developing policies that support the transformation of contextual and relevant Islamic learning. Novelty in the context of an integrated exploration of various dimensions of innovation in Islamic education within the Merdeka Curriculum framework. Previous research tends to only address one or two aspects, this study systematically combines five domains of innovation.